Capacity Of Firefighters Fire Fighting Officers In The Implementation Of The Sister Village Program - Dwi Agustina; Eka Rofiyanti (Yayasan Ilomata, 2020)
Fire is one of the dangers that can threaten cities that have dense residential. DKI Jakarta as the capital city of the country with many dense residential areas with a high level of fire risk, this is proven from the data of 948 fires occurred from 2011, they were1008 in 2012, 486 in 2013, 486 in 2014 696, 1582 in 2015 and in 2016 there were 1139 fires. The trigger of fires in dense residential areas was the lack of resilience in handling the fire disasters, resilience here refers to reducing the vulnerability that becomes a potential fire hazard in residential areas. Community involvement in fire disaster risk reduction is very important, this should be with the capacity of firefighters to be able to initiate the community to be involved in fire disaster risk reduction efforts. This research will analyze the capacity of firefighters in implementing the Sister Village program, identify the capacity of implementing the Sister Village program that was seen from (i) the capacity of firefighters in initiating communities to play a role in efforts to reduce the risk of fire disasters, (ii) Implementation of the Sister Village Program in fire disaster risk reduction efforts, (iii) Community involvement in fire disaster risk reduction efforts in DKI Jakarta. In doing research the capacity of firefighters in the application of the Sister Village Program as an effort to reduce the risk of fire disasters used descriptive qualitative research methods.